Disassembled Food Webs and Messy Projections: Modern Ungulate Communities in the Face of Unabating Human Population Growth - Berger, Joel; Wangchuk, Tshewang; Briceño, Cristobal; Vila, Alejandro; Lambert, Joanna E. (Frontiers in Ecology and Evolution, 2020)
The human population grows inexorably. When Charles Darwin explored the southern cone of South America in 1830, fewer than 1.2 billion people inhabited Earth. When Ehrlich’s Population Bomb appeared in 1968 there were 3.5 billion. We approach eight billion today, and biospheric impacts do not abate. We’ve affected most life forms through climate modification, harvest, erasure and fragmentation of habitat, disease, and the casting of alien species. Given the lack of abatement in human population growth, herein we focus on the modalities of ecological disruption – direct and indirect – that mitigate the changing role of ungulates in landscapes. Much of what was once generally predictable in terms of pattern and process is no longer. Offshore climatic events have strong onshore consequence, as exemplified by toxic algal blooms in the Patagonian Pacific. These have diminished the harvest of fish and likely resulted in fisherman using dogs to hunt huemul (Hippocamelus bisulcus), the most endangered large terrestrial mammal of the Western Hemisphere. Similarly, human economies foment change in the Himalayan realm and Gobi Desert by increasing numbers of cashmere-producing goats, and where dogs that once followed tourists or guarded livestock they now hunt a half dozen threatened, endangered, and rare ungulates including kiang (Equus kiang) and chiru (Pantholops hodgsonii), saiga (Saiga tatarica) and takin (Budorcas taxicolor), spread disease, and displace snow leopards (Panthera uncia). In North America’s Great Basin Desert, one hundred years of intense livestock grazing created a phase shift by which changed plant communities enabled mule deer (Odocoileus hemionus) colonization. An altered predator-prey system ensued with the arrival of pumas (Panthera concolor). Patterns of resilience postulated by Hollings (1973) become more difficult to witness in the absence of humans as our domination of earth destabilizes systems beyond return points. These include ungulates both in and out of protected areas. Consequently, only messy projections of future community reorganization seem reasonable whether related to food webs or assembly rules that once governed ungulate communities of the very recent past.